Competition for nitrogen between trees in a mixed-species plantation in the Solomon Islands. Issue 3 (17th May 2017) - Vigulu, V. W.; Blumfield, T. J.; Reverchon, F.; Xu, Z. H.; Tutua, S. S.
ABSTRACT: As part of an ACIAR project aiming at improving community forestry in Solomon Islands, mixed-species plantations were established to assess the feasibility of inter-planting teak ( Tectona grandis L. f.) and flueggea ( Flueggea flexuosa Muell. Arg). Flueggea is a native hardwood used for timber and fence construction, and early removal of flueggea from a mixed-species stand could have a similar silvicultural outcome to thinning a single-species stand of teak. Using 15 N-labelled ammonium sulphate, we investigated the competition for nitrogen (N) between the two species. The 15 N-labelled tracer was applied to the soil surface of plots containing pairs of trees, one of each species, in 2-year-old and 4-year-old mixed-species stands, after the pairs of trees were isolated from the rest of the stand by an impermeable membrane. After 12–18 months, the isolated trees were measured and harvested, and each tree component (roots, stem, branch and foliage) was weighed and analysed for total N and 15 N enrichment. There was no significant difference in the amounts of 15 N between teak and flueggea components at either age, suggesting equal uptake of added 15 N-labelled tracer by both species. The 15 N amount was greater in stem followed by root, foliage and branch for teak and branch followed by stem, root and foliage for flueggea. About 42% and 55% of the applied 15 N tracer were recovered in the 2-year and 4-year plots respectively, suggesting that higher uptake occurs with well-established root structure and that N losses decreased following canopy closure. The amount of total nitrogen was not significantly different between teak and flueggea components at age 2 and 4 years, and may indicate equal access to growth resources, and similar allocation. Although teak had significantly greater stem growth (height, basal area and volume) than flueggea in the 4-year plots, 15 N uptake were similar to flueggea, which may mean that competition for growth resources was still minimal or that access to the resources was equal and growth rates differed between species.